Identifying and Treating Opioid Side Effects: The Development of Methylnaltrexone - Moss, Jonathan (Anesthesiology (Philadelphia), 2019)
Methylnaltrexone Reverses Chronic Opioid-induced ConstipationA Randomized, Controlled Trial. By Yuan CS, Foss JF, O’Connor M, Osinski J, Karrison T, Moss J, Roizen MF. JAMA 2000; 130:142–8. Reprinted with permission. CONTEXT:Constipation is the most common chronic adverse effect of opioid pain medications in patients who require long-term opioid administration, such as patients with advanced cancer, but conventional measures for ameliorating constipation often are insufficient. OBJECTIVE:To evaluate the efficacy of methylnaltrexone, the first peripheral opioid receptor antagonist, in treating chronic methadone-induced constipation. DESIGN:Double-blind, randomized, placebo-controlled trial conducted between May 1997 and December 1998. SETTING:Clinical research center of a university hospital. PARTICIPANTS:Twenty-two subjects (9 men and 13 women; mean [SD] age, 43.2 [5.5] years) enrolled in a methadone maintenance program and having methadone-induced constipation. MAIN OUTCOME MEASURES:Laxation response, oral-cecal transit time, and central opioid withdrawal symptoms were compared between the 2 groups. RESULTS:The 11 subjects in the placebo group showed no laxation response, and all 11 subjects in the intervention group had laxation response after intravenous methylnaltrexone administration (P<.001). The oral-cecal transit times at baseline for subjects in the methylnaltrexone and placebo groups averaged 132.3 and 126.8 minutes, respectively. The average (SD) change in the methylnaltrexone-treated group was −77.7 (37.2) minutes, significantly greater than the average change in the placebo group (−1.4 [12.0] minutes; P<.001). No opioid withdrawal was observed in any subject, and no significant adverse effects were reported by the subjects during the study. CONCLUSIONS:Our data demonstrate that intravenous methylnaltrexone can induce laxation and reverse slowing of oral cecal-transit time in subjects taking high opioid dosages. Low-dosage methylnaltrexone may have clinical utility in managing opioid-induced constipation.